Correction by Laennec of chronic iron overload liver, kidneys and brain - O. A. Nazarenko; O. A. Gromova; T. R. Grishina; I. Yu. Torshin; V. I. Demidov; I. K. Tomilova; E. L. Aleksakhina; I. V. Gogoleva (Фармакокинетика и Фармакодинамика)
The results of experimental investigations of the effects of Laennec on chronic iron overload. Long-term (2 weeks) application of iron sulfate or iron polymaltose complex composition caused chronic iron overload (hemosiderosis). The liver and kidneys is more pronounced when using iron sulfate and a few less - when using polymaltose complex. Laennec decreased the damage of hepatocytes (decreased ALT levels). According to histological analysis application Laennec reduced iron deposition in the liver and kidneys and completely prevented the formation of iron deposits in the brain.